Presentation and unveiling of the memorial tablets commemorating the Lincoln and Burns event (November 19, 1863): held at the Presbyterian Church, Gettysburg, Pa., Nov. 19th, 1914 (Gettysburg compiler (Gettysburg, Pa. : 1914), 1916)
Address of Dr. T.C. Billheimer -- John Burns of Gettysburg / Lyman Whitney Allen -- Presentation address of Col. E.B. Cope / read by Judge S. McC. Swope -- Unveiling of the tablets on Lincoln pew -- Presentation address of John White Johnston -- Acceptance of memorial tablets / Rev. F.E. Taylor -- Address / Judge Wm. MacLean -- Reminiscences: Capt. Ziegler's letter ; Hon. Wm. H. Tipton ; Hon. Theodore MacAlister ; W.A. MacIlhenny ; John E. Pitzer ; Miss Agnes McCreary.